2009
DOI: 10.1007/s11010-009-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates sensitize the effect of chemotherapeutic drugs via modulation of protein kinase C and telomerase in cervical cancer cells

Abstract: Isothiocyanates have potential chemopreventive and antitumor effects. In the present study, we examined the actions of PEITC and sulphoraphane in modulating the activity of protein kinase C (PKC) and telomerase in cervical cancer cell line HeLa. These tumor markers are highly activated in human cancers. These compound efficiently downregulated the antiapoptotic isoforms (PKC-alpha, -betaII, -epsilon, and -zeta) as well as telomerase, whereas the proapoptotic form (PKC-delta) was upregulated. Studies were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…In recent years, a number of mechanisms have been proposed for the activities of AITC [25][26][27][28][29][30][31][32][33], such as microtubule, proteasome, nucleus, mitochondria, ABC transportes and TPR channel. However, identifying the molecular targets is a first step to make sure the molecular mechanisms of AITC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of mechanisms have been proposed for the activities of AITC [25][26][27][28][29][30][31][32][33], such as microtubule, proteasome, nucleus, mitochondria, ABC transportes and TPR channel. However, identifying the molecular targets is a first step to make sure the molecular mechanisms of AITC.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of metformin and PEITC showed high efficacy in cisplatin resistant cancer cells [145]. PEITC and SFN enhanced the apoptotic effects of Adriamycin and etoposide by inhibition of protein kinase C [146]. SFN also increased the susceptibility of Adriamycin to resistant cells [144].…”
Section: Combination Therapymentioning
confidence: 99%
“…Often, cancer cells exploit telomerase enzyme to alter the length of telomeres rendering them immortal [128]. PEITC has been shown to inhibit telomerase activity in prostate and cervical cancer cells [129, 130]. Furthermore, it was observed that pre-treatment with PEITC induced apoptosis as well as increased the efficacy of adriyamycin and etoposide by inhibiting protein kinase C and telomerase [130].…”
Section: Anti-cancer Activity Of Peitcmentioning
confidence: 99%